The role of the driving dynamics beyond RDE limits and DPF regeneration events on pollutant emissions of a Euro 6d-temp passenger vehicle. (March 2022) - Toumasatos, Z.; Raptopoulos-Chatzistefanou, A.; Kolokotronis, D.; Pistikopoulos, P.; Samaras, Z.; Ntziachristos, L.
Abstract: The current study investigates gaseous and particulate emissions of a diesel passenger car (Euro 6d-temp ), under specific operation events, including diesel particulate filter (DPF) active regeneration. The contribution of DPF active regeneration to sub-23nm volatile and solid particle emissions was investigated in a dedicated measurement campaign. A novel exhaust gas sampling and dilution system was employed for the determination of solid particle number (SPN) emissions down to 23 nm, 10 nm, and 2.5 nm. Total particle number (TPN) emissions, including semi-volatiles, down to 10 nm and down to 5.6 nm were also measured. A DPF active regeneration was triggered during real driving emissions (RDE) testing. DPF regeneration increased NOx and SPN down to 23 nm (SPN23) by 1.7 times and 3 orders of magnitude, respectively, compared to non-regenerating conditions. A second DPF regeneration was triggered during steady-state conditions in the laboratory. Once again, SPN23 emissions were at least 3 orders of magnitude higher compared to normal operation. Under regeneration conditions, SPN down to 2.5 nm (SPN2.5) was 2.3 times higher than SPN23, which suggests that a significant number of particles reside below the regulated limit of 23 nm during DPF regeneration. Moreover, TPN emissions were at least 7 times higher than SPN ones. Both these observations suggest that a significant number of particles during DPF regeneration evades current SPN23 regulation. Based on the DPF active regeneration findings in RDE and lab conditions, the current study introduces an enhanced particulate emission factor that includes the impact of active DPF regenerations. Graphical abstract: Image 1 Highlights: Significant number of particles during regeneration evades current SPN23 regulation. Up to an order of magnitude higher TPN10 than SPN10 during active regeneration. Passive regeneration contributes up to 100 times higher SPN23 than normal operation. Enhanced EF suggests up to 3.9 times higher SPN23 based on regeneration findings.